Analisis Struktur dan Profil Vegetasi Mangrove di Kecamatan Sayung Kabupaten Demak - ALIFIANSYAH, JUANDRA; Irsadi, Andin; Kartijono, Nugroho Edi; Ngabekti, Sri (Universitas Negeri Semarang, 2024)
Sayung District is one of the district in Demak Regency which has mangrove vegetation. The alteration of Demak Regency's coastal areas caused by the sea rob phenomenon has a significant impact on the mangrove vegetation. The Semarang-Demak toll road construction along Sayung coast potentially causes mangrove damage. The purpose of this study is to determine the structure and profile, and analyze the condition of mangrove vegetation in Sayung, based on the structure and profile of Sayung mangrove vegetation. The study was conducted on the mangroves of Bedono, Mondoliko, and Morosari Village. This research used an exploratory method with descriptive analysis, by collecting data on vegetation parameters and vegetation profiles. The results showed that the types of mangroves found at all observation stations consisted of Avicennia, Bruguiera, and Rhizophora. The profile graph shows an association between Avicennia alba, Avicennia marina, and Rhizophora mucronata. Important Value Index (IVI) for all stations shows that Avicennia officinalis have highest value on 65,30 and 50,18 respectively. Diversity index shows that both stations have value on 0,873 and 0,893 which belongs to low diversity. Similarity index on each sub-stations shows the significant difference between Bedono-A, Bedono-C, Mondoliko, and Morosari stations at 0,4 index, Based on Abiotic parameters such as pH, salinity, and water temperature found on the optimal quality standard level. The conclusion is mangrove vegetation structure dominated by Avicennia and Rhizophora groups, with a low level of diversity at all observation stations.